Role of Tumor Tissue Analysis in Rectal Cancer Pharmacogenetics - Balboa, Emilia; Duran, Goretti; Lamas, Maria Jesus; Gomez-Caamaño, Antonio; Celeiro-Muñoz, Catuxa; Lopez, Rafael; Carracedo, Angel; Barros, Francisco (IntechOpen, 2011)
None